Are increased oxidative stress and asymmetric dimethylarginine levels associated with masked hypertension?. (2nd April 2016) - Inan, Bayram; Ates, Ihsan; Ozkayar, Nihal; Kundi, Harun; Topcuoglu, Canan; Dede, Fatih; Sennaroglu, Engin
ABSTRACT: Objective: In this study, our aim was to determine total oxidative stress and asymmetric dimethylarginine (ADMA) levels in patients with masked hypertension (MHT) and to examine their association with blood pressure. Methods: Fifty patients diagnosed with MHT and 48 healthy volunteers without any known chronic diseases have been included in this study. Results: When compared to the control group, patients with MHT had higher levels of mean ADMA ( p < 0.001), total oxidant status (TOS) ( p < 0.001), and oxidative stress index (OSI) ( p < 0.001), and a lower mean total antioxidant status (TAS) ( p < 0.001) level. While a positive correlation was determined between the systolic blood pressure (SBP) and diastolic blood pressure (DBP) levels with ADMA, TOS, and OSI levels, a negative correlation was determined with the TAS level. During the stepwise multivariable logistic regression analysis, age (OR = 1.221; p = 0.003), body mass index (OR = 1.512; p = 0.005), low density lipoprotein (OR = 0.925; p = 0.016), ADMA (OR = 1.200; p = 0.002), and OSI (OR = 3.750; p = 0.002) levels were determined to be the predictors of MHT. During the linear regression analysis, it was determined that the independent risk factors of SBP and DBP are ADMA and OSI, and the independent risk factor of TOS, OSI, and ADMA is SBP. Our study found out that oxidative stress and ADMA levels of patients with MHT are higher than those of the control group. ADMA and OSI were determined to be predictors of MHT. Conclusion: Based on these results, it could be said that oxidative stress, and therefore the ADMA level, could have an effect on the etiopathogenesis of MHT.